THE INFLUENCE OF THE NUMBER OF TOURISTS ON REGIONAL ORIGINAL REVENUE WITH HOTEL TAX REVENUE AS A MEDIATING VARIABLE - Astuti Purnamawati; Algifari; Theresia Trisanti; Conny Tjandra Rahardja (LPPM STIE YKPN Yogyakarta, 2026)
This study aims to examine the effect of the number of tourists on Regional Original Revenue (PAD) in the Special Region of Yogyakarta, with hotel tax revenue as a mediating variable. The research uses a quantitative approach with monthly secondary data from 2019 to 2023 obtained from official government sources. The analysis was conducted using the Hayes PROCESS regression model to test both direct and indirect relationships among variables. The results show that the number of tourists does not have a significant direct effect on PAD. However, the number of tourists has a significant positive effect on hotel tax revenue, and hotel tax revenue significantly influences PAD. Furthermore, mediation analysis indicates that hotel tax revenue successfully mediates the relationship between the number of tourists and PAD. This finding suggests that the contribution of tourism to regional revenue occurs indirectly through fiscal instruments, particularly hotel tax. These results highlight the importance of effective tax management in optimizing the economic benefits of tourism. Strengthening tax collection systems and improving fiscal governance are essential to enhance regional financial capacity. Future research is recommended to include other mediating variables and extend the observation period for a more comprehensive analysis.